Increases in Colonic Bacterial Diversity after ω-3 Fatty Acid Supplementation Predict Decreased Colonic Prostaglandin E2 Concentrations in Healthy Adults. Issue 7 (3rd May 2019) - Djuric, Zora; Bassis, Christine M; Plegue, Melissa A; Sen, Ananda; Turgeon, D Kim; Herman, Kirk; Young, Vincent B; Brenner, Dean E; Ruffin, Mack T
ABSTRACT: Background: The intestinal microbiome is an important determinant of inflammatory balance in the colon that may affect response to dietary agents. Objective: This is a secondary analysis of a clinical trial, the Fish Oil Study, to determine whether interindividual differences in colonic bacteria are associated with variability in the reduction of colonic prostaglandin E2 (PGE2 ) concentrations after personalized supplementation with ω-3 (n–3) fatty acids. Methods: Forty-seven healthy adults (17 men, 30 women, ages 26–75 y) provided biopsy samples of colonic mucosa and luminal stool brushings before and after personalized ω-3 fatty acid supplementation that was based on blood fatty acid responses. Samples were analyzed using 16S ribosomal RNA sequencing. The data analyses focused on changes in bacterial community diversity. Linear regression was used to evaluate factors that predict a reduction in colonic PGE2 . Results: At baseline, increased bacterial diversity, as measured by the Shannon and Inverse Simpson indexes in both biopsy and luminal brushing samples, was positively correlated with dietary fiber intakes and negatively correlated with fat intakes. Dietary supplementation with ω-3 fatty acids increased the Yue and Clayton community dis-similarity index between the microbiome in luminal brushings and colon biopsy samples post-supplementation ( P = 0.015). In addition, there was a small group of individuals with relatively high Prevotella abundance who were resistant to the anti-inflammatory effects of ω-3 fatty acid supplementation. In linear regression analyses, increases in diversity of the bacteria in the luminal brushing samples, but not in the biopsy samples, were significant predictors of lower colonic PGE2 concentrations post-supplementation in models that included baseline PGE2, baseline body mass index, and changes in colonic eicosapentaenoic acid–to–arachidonic acid ratios. The changes in bacterial diversity contributed to 6–8% of the interindividual variance in change in colonic PGE2 ( P = 0.001). Conclusions: Dietary supplementation with ω-3 fatty acids had little effect on intestinal bacteria in healthy humans; however, an increase in diversity in the luminal brushings significantly predicted reductions in colonic PGE2 . This trial was registered at www.clinicaltrials.gov as NCT 01860352.